The effect of performance appraisal dimensions On organization confidence - فندي, علي حسون; طاهر, فاضل جميل; سلمان, فاضل حمد (Journal of Economics and Administrative Sciences, 2012)
This research was designed to study effect of performance appraisal dimensions on organizational confidence.Asset completion questionnaire was used to collect data of this research from a random simple represent forty employees who works in Iraqi Oil ministry. The main result of this research was positive relations and the effect between performance appraisal and organizational confidence. The research contains some conclusions, the main of it is unimplemented the performance appraisal results in the policies of employees in the ministry and it work in classic methods incentives and training.The important recommendations must doing to achieve integrating between the result of performance appraisal and policies of individuals.